Hodnocení efektivity sociálních služeb pro duševně nemocné - Hejzlar, Petr; Halíř, Martin; Herelová, Hana (Univerzita Pardubice, 2011)
The article concerns with advantages for professional social services´development thank to effectivness review. It comments and explain the implementation of Camberwell Assessement of Needs into community mental health care services provider´s evaluation process. The study results are presented.
Keywords: community services for mentally Ill; effectivness evaluation; assessment of need